Can oceanic prey effects on growth and time to fledging mediate terrestrial predator limitation of an at‐risk seabird?. Issue 10 (5th October 2020) - Knudson, Timothy W.; Lovvorn, James R.; Lawonn, M. James; Corcoran, Robin M.; Roby, Daniel D.; Piatt, John F.; Pyle, William H.
Abstract: Most seabird species nest colonially on cliffs or islands with limited terrestrial predation, so that oceanic effects on the quality or quantity of prey fed to chicks more often determine nest success. However, when predator access increases, impacts can be dramatic, especially when exposure to predators is extended due to slow growth from inadequate food. Kittlitz's Murrelet ( Brachyramphus brevirostris ), a rare seabird having experienced serious declines, nests solitarily on the ground in barren, often alpine areas where exposure to predators is generally low. Nestling growth rates are exceptionally high and nestling periods very short relative to other Alcidae. This strategy reduces duration of exposure to predators, but demands adequate deliveries of high‐energy prey. In an area where foxes can access nests, we investigated whether varying energy content of prey fed to chicks could alter growth rates and resulting duration of predator exposure, and whether prolonged exposure appreciably reduced nest success. From 2009 to 2016, we monitored 139 nests; 49% were depredated (almost all by foxes) and 25% fledged. Prey fed to nestlings were 80% Pacific sand lance ( Ammodytes personatus ) and 19% capelin ( Mallotus villosus ), with capelin having 2.3× higher energy content per fish. In a year of slow chick growth, increased sand lance energy density of 31% (4.29–5.64 kJ/g, within published values), or increased proportion of capelin in the diet from 5.6% to 27.2%, would have allowed maximum chick growth. Maximum growth rates were attainable by delivering only 1.9 capelin/d versus 5.5 sand lance/d. Slow growth increased time to fledging by up to 5 d, decreasing survival by 7.7% (0.142–0.131). Breeding propensity of Kittlitz's Murrelet averages only 20%, so even small changes in nest success could affect populations. Although nest success was limited mainly by predation, oceanic effects on prey quantity and quality had overriding impacts in one year (2015 heat wave), and small but substantive effects in other years by mediating exposure to predation. Climate warming that decreases availability of high‐energy forage fish, or increases expansion of predators into nesting habitats, may disproportionately affect this sensitive species and others with predator‐accessible nests and demands for energy‐rich prey.